Cancer de la prostate - Yahya bey, Hafida; Behih, Malika (My University, 2018)
Cancer is a highly feared multifactorial disease whose number reached by this pathology continues to increase. The most known cancer in humans after poumon cancer is prostate cancer. It is the second leading cause of death in humans. This type of cancer has many known causes and other unknown ones where age and genetic factors are the most favorable. The diagnosis of prostate cancer is based on the PSA (Prostate Specific Antigen) assay, accompanied by an extension assessment. The discovery of the disease is accompanied with urinary disorders and alteration of the general condition (weight loss). This public health problem is becoming more and more important because of the increase in life expectancy.
Keywords: Cancer; prostate; PSA; Public health; Cancer; prostate; PSA; Santé publique